Occipital Nerve Stimulation for Refractory Chronic Cluster Headache: A Cost‐Effectiveness Study. Issue 6 (22nd April 2021) - Bulsei, Julie; Leplus, Aurélie; Donnet, Anne; Regis, Jean; Lucas, Christian; Buisset, Nadia; Raoul, Sylvie; Guegan‐Massardier, Evelyne; Derrey, Stéphane; Jarraya, Bechir; Valade, Dominique; Roos, Caroline; et al.
Abstract: Introduction: Occipital nerve stimulation (ONS) is proposed to treat refractory chronic cluster headache (rCCH), but its cost‐effectiveness has not been evaluated, limiting its diffusion and reimbursement. Materials and Methods: We performed a before‐and‐after economic study, from data collected prospectively in a nation‐wide registry. We compared the cost‐effectiveness of ONS associated with conventional treatment (intervention and postintervention period) to conventional treatment alone (preintervention period) in the same patients. The analysis was conducted on 76 rCCH patients from the French healthcare perspective at three months, then one year by extrapolation. Because of the impact of the disease on patient activity, indirect cost, such as sick leave and disability leave, was assessed second. Results: The average total cost for three months was €7602 higher for the ONS strategy compared to conventional strategy with a gain of 0.07 quality‐adjusted life‐years (QALY), the incremental cost‐effectiveness ratio (ICER) was then €109, 676/QALY gained. The average extrapolated total cost for one year was €1344 lower for the ONS strategy ( p  = 0.5444) with a gain of 0.28 QALY ( p  < 0.0001), the ICER was then €‐4846/QALY gained. The scatter plot of the probabilistic bootstrapping had 80% of the replications in the bottom right‐hand quadrant, indicating that the ONS strategy is dominant. The average indirect cost for three months was €377 lower for the ONS strategy ( p  = 0.1261). Discussion: This ONS cost‐effectiveness study highlighted the limitations of a short‐time horizon in an economic study that may lead the healthcare authorities to reject an innovative strategy, which is actually cost‐effective. One‐year extrapolation was the proposed solution to obtain results on which healthcare authorities can base their decisions. Conclusion: Considering the burden of rCCH and the efficacy and safety of ONS, the demonstration that ONS is dominant should help its diffusion, validation, and reimbursement by health authorities in this severely disabled population.